Biofuel From Cow Tallow: A Case Study - Abdulrahman, Ribwar K; Zangana, Mohammed H; Ali, Jafar A; Aziz, Rebwar Ibrahim; Karem, Rawaz M; Hussain, Balen M. (European Scientific Journal, ESJ, 2016)
The global demand for energy in recent decade has been dramatic. Indeed, several oil and gas reservoirs around the world are depleted every day. Moreover, the fossil fuels for example, petroleum emitted huge quantities of toxic gases to the environment. Therefore, the passive environmental consequences of fossil fuels and the bother about fossil fuel supplies have encouraged the investigation for renewable biofuels. Thus, this work is objective to produce a biodiesel fuel from residual cow tallow that produced every day at Koya city slaughterhouse. The Koya slaughterhouse cow tallow may consider low cost renewable feed stock to produce biodiesel. Furthermore, the study has examined various process parameters for example, catalyst amount and alcohol amount as well on fuel production yield. The produced biodiesel is also subjected into several tests for instance, density and cetane number.